Plasma biomarkers of decreased vesicular storage distinguish Parkinson disease with orthostatic hypotension from the parkinsonian form of multiple system atrophy - Goldstein, David S.; Kopin, Irwin J.; Sharabi, Yehonatan; Holmes, Courtney (Clinical autonomic research, 2015)
Background Parkinson disease with orthostatic hypotension (PD + OH) and the parkinsonian form of multiple system atrophy (MSA-P) can be difficult to distinguish clinically. Recent studies indicate that PD entails a vesicular storage defect in catecholaminergic neurons. Although cardiac sympathetic neuroimaging by 18 F-dopamine positron emission tomography can identify decreased vesicular storage, this testing is not generally available. We assessed whether plasma biomarkers of a vesicular storage defect can separate PD + OH from MSA-P. Methods We conceptualized that after F-dopamine injection, augmented production of F-dihydroxyphenylacetic acid (F-DOPAC) indicates decreased vesicular storage, and we therefore predicted that arterial plasma F-DOPAC would be elevated in PD + OH but not in MSA-P. We measured arterial plasma F-DOPAC after 18 F-dopamine administration (infused i.v. over 3 min) in patients with PD + OH ( N = 12) or MSA-P ( N = 21) and in healthy control subjects ( N = 26). Peak F-DOPAC:dihydroxyphenylglycol (DHPG) was also calculated to adjust for effects of denervation on F-DOPAC production. Results Plasma F-DOPAC accumulated rapidly after initiation of 18 F-dopamine infusion. Peak F-DOPAC (5–10 min) in PD + OH averaged three times that in MSA-P ( P < 0.0001). Among MSA-P patients, none had peak F-DOPAC > 300 nCi-kg/cc-mCi, in contrast with 7 of 12 PD + OH patients ( χ 2 = 16.6, P < 0.0001). DHPG was lower in PD + OH (3.83 ± 0.36 nmol/L) than in MSA-P (5.20 ± 0.29 nmol/L, P = 0.007). All MSA-P patients had peak F-DOPAC:DHPG < 60, in contrast with 9 of 12 PD + OH patients ( χ 2 = 17.5, P < 0.0001). Adjustment of peak F-DOPAC for DHPG increased test sensitivity from 58 to 81 % at similar high specificity. Interpretation After F-dopamine injection, plasma F-DOPAC and F-DOPAC:DHPG distinguish PD + OH from MSA-P.